Ecological and genetic variation in reef‐building corals on four Society Islands. (4th February 2016) - Edmunds, Peter J.; Leichter, James J.; Johnston, Erika C.; Tong, Eric J.; Toonen, Robert J.
Abstract: We quantified benthic community structure on shallow (10 m isobath) reefs separated by 3–130 km on four islands in the south Pacific, and evaluated the roles of disturbances vs. coral recruitment as causes of spatial heterogeneity. Reefs were surveyed in 2013 on Moorea, Tahiti, Tetiaroa, and Maiao, with community structure sampled at two sites on each island using photoquadrats. The effects of coral recruitment on population structure were evaluated through genetic analyses of Pocillopora on three of the islands. Benthic community structure with functional group resolution differed among islands and generally among sites, but coral community structure (generic resolution) differed among islands, but generally not among sites. Genetic analyses of Pocillopora using the open reading frame of host mtDNA revealed varying relative abundances of Pocillopora meandrina/Pocillopora eydouxi, Pocillopora verrucosa, Pocillopora effuses, and two unnamed haplotypes on each island. These results suggest that corals on each island represent unique samplings of genetically discrete larval assemblages rather than random samplings of a single larval assemblage. Together, our findings emphasize the extent to which coral community structure varies over a scale of <200 km, and suggests that recruitment from spatially discrete pools of coral larvae plays an important role in creating spatial variation in community structure, even where reefs are connected by prevailing currents.